TYPES AND FUNCTIONS OF TABOO WORDS FOUND IN LIL DICKY’S SONG ON ALBUM PROFESSIONAL RAPPER - Mariyanto, I Komang; Sulatra, I Komang; Ayomi, Putu Nur (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
This study focuses on analysing the types and function of taboo words found in Lil Dicky’s Song on Album Professional Rapper. The data source was taken from Lil Dicky’s Song on Album Professional Rapper it was released on July 31, 2015. Descriptive qualitative method was used in this study to describe the use of taboo words in song lyrics. In this study, the descriptive qualitative method was used to describe the use of taboo words in song lyrics. The method was used to offer a clear analysis of the data based on the theory. This study employed the theory from Batistella (2005) which is proposed to analyse the type of taboo words found in Lil Dicky’s Song on Album Professional Rapper and the theory from Wardhaugh (2006) which is proposed to analyse the functions of taboo words found in Lil Dicky’s Song on Album Professional Rapper. Based on the analyses there are 295 data about the types and functions of taboo words found. There are four types of taboo words found those are epithet, profanity, vulgarity and obscenity. Obscenity becomes the most types found in the lyrics of the song which found 152 times. And Profanity becomes the least types found which is found 19. And four functions of taboo words are found in the song lyrics those are to show contempt, to draw attention to oneself, to be provocative, and to mock authority. The most function found is to show contempt which is found 107 times and to mock authority becomes the least functions with only found 3 times. Keywords: Taboo words, Types, Functions, Song lyrics